PHARMACOLOGICAL CORRECTION OF INTERCEPT HEMODYNAMICS IN ACUTE KIDNEY DAMAGE (PART 1) - Katherine Shramenko; Georgiy Gorodnik; Valentina Shano; Irina Kuznetsova; Aleksandr Grigorenko; Vladimir Potapov (Research Results in Pharmacology, 2017)
Introduction: Development of vasoconstriction of kidney arterioles and reduction of renal blood flow is one of the main mechanism of acute kidney injury (AKI) formation. Methods for evaluation of intrarenal hemodynamics status are rather limited. Evident interest for the clinician is the possibility of rapid and non-invasive assessment of renal hemodynamics using the dopplerography method. The method makes it possible to visualize the kidney vessels and conduct a qualitative and quantitative evaluation of renal blood flow. Peculiarities of disturbed blood flow in the kidneys can determine the individuality of pharmacological correction and intensive care in patients with AKI.